2020
DOI: 10.1186/s12871-020-01019-5
|View full text |Cite
|
Sign up to set email alerts
|

LMA® Gastro™ Airway for endoscopic retrograde cholangiopancreatography: a retrospective observational analysis

Abstract: Background: Various airway techniques have been employed for endoscopic procedures, with an aim to optimise patient outcomes by improving airway control and preventing hypoxia whilst avoiding the need for intubation. The LMA® Gastro™ Airway, a novel dual channel supraglottic airway technique, has been described as such a device. Its utility alongside sedation with low flow nasal cannula and general anaesthesia (GA) with intubation for endoscopic retrograde cholangiopancreatography (ERCP) procedures was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…A previous article on the use of the GLMA describes the successful use of the GLMA without difficulties. [ 3 ] However, our bench observation suggests the contrary. Furthermore, our solution provides a simple way to overcome the problem of manoeuvreability of the duodenoscope through the “gastro” channel.…”
mentioning
confidence: 56%
“…A previous article on the use of the GLMA describes the successful use of the GLMA without difficulties. [ 3 ] However, our bench observation suggests the contrary. Furthermore, our solution provides a simple way to overcome the problem of manoeuvreability of the duodenoscope through the “gastro” channel.…”
mentioning
confidence: 56%
“…The authors have been regularly using the device for the last 3 years, and it is evident that an airtight seal is possible by choosing an appropriate size. [15,18]. In our own experience (MS) during the peak of the pandemic in northern Italy, we found that LMA ® Gastro™ was a valuable device.…”
Section: To the Editorsmentioning
confidence: 70%
“…This can lead to hypoxemia and warrants the need of rescue airway. LMA® Gastro™ can be successfully employed as a primary airway technique for such procedures [101].…”
Section: Size Selection Practical Aspectmentioning
confidence: 99%